PERAN KARAKTERISTIK APARAT PENGAWAS INTERNAL PEMERINTAH TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH DENGAN KOMITMEN SEBAGAI VARIABEL PEMODERASI - Darmawan, Dadan; Yazid, Helmi; Bastian, Elvin (Badan Perencanaan Pembangunan Daerah Provinsi Banten, 2022)
Accountability is one of the keys to achieving good governance and aims to measure how well the Government Agencies carry out their main tasks and use the budget. The evaluation value of the Banten Province AKIP from year to year tends to increase, but is not significant. The growth of the Banten Province SAKIP Value from 2016 to 2017 was only 0.03. Meanwhile, the growth of SAKIP Value from 2017 to 2018 was 4.30. Presidential Decree No. 29 of 2014 explains that the Government Internal Supervisory Apparatus (APIP) is given more authority to play a role in achieving local government performance. This study aims to analyze and examine the Effect of the Characteristics of Assistance for Government Internal Supervisory Apparatus (APIP) on the Performance Accountability of Government Agencies (AKIP). Several factors that greatly affect APIP's performance become independent variables in this study, namely the level of APIP capability, the number of APIP with Management Commitment as moderating. Sampling used purposive sampling method with 61 respondents consisting of Government Agencies Performance Accountability Reporters (LAKIP) in 42 Banten Provincial Government Officials and 29 APIP Banten Provincial Inspectorates in charge of evaluating LAKIP. The data analysis technique used the Partial Least Square (PLS) approach. The results of this study state that the APIP Capability Level has an effect on the Performance Accountability of Government Agencies (AKIP), while the number of APIPs does not affect the Performance Accountability of Government Agencies (AKIP) and Management Commitment does not moderate the APIP Capability Level on the Performance Accountability of Government Agencies (AKIP), but moderating the Number of APIP Personnel on the Performance Accountability of Government Agencies (AKIP).